Chretien continued a study of the Conte du Graal and its verse continuations - Bruckner, Matilda Tomaryn (Oxford University Press, 2008)
Chretien de Troyes's grail story 'Conte du Graal' generated numerous rewritings from the late 12th to the 15th centuries. This book shows how Chretien's verse continuators used his narrative techniques to ask the questions about love, chivalry religion, and violence that entered Arthurian romance in the first 'story of the grail'.